The Contribution of Knowledge Management Practices for Developing Dynamic Capabilities: Exploring Routines in the Services Sector. Issue 1 (2nd January 2022) - Hattore, Jessica Ramirez; Damke, Elói Junior; Ferasso, Marcos; Dechechi, Eduardo César
Abstract: The purpose of this manuscript is to identify the contribution of knowledge management practices for developing dynamic capabilities in a service sector company. For this case study, the dataset comprised ten interviews with company employees and managers and was analyzed using a pattern-matching technique based on the literature. The main findings were that the company mapped its organizational actions in each process of knowledge management, which was the basis for the development of its dynamic capabilities. The development of such capabilities enabled the company to analyze possible applications and improve the existing routines.